Determinants and Standardization of Mesopic Visual Acuity - Lin, Rachelle J.; Ng, Jason S.; Nguyen, Andrew L. (Optometry and vision science, 2015)
PURPOSEIt is well established that visual acuity (VA) decreases with luminance but the specific factors that are responsible remain unclear. The purpose of this study was to quantify the contributions of accommodative error, pupil size, and higher-order aberrations to the decrease in VA when transitioning from photopic to mesopic light levels. Additionally, repeatability of VA at photopic and mesopic levels was measured to derive a luminance recommendation for mesopic VA testing, which can provide the standardization needed for future translational clinical studies and the widespread adoption of mesopic VA testing. METHODSMonocular VAs were assessed at one photopic and three mesopic light levels94, 3, 0.75, and 0.38 cd/m, with an E-ETDRS testing system in 43 normal subjects. Accommodative error, pupil size, and higher-order aberrations were obtained. Twenty subjects were retested at another visit to assess VA repeatability. RESULTSThe mean (±SD) logMAR (logarithm of the minimum angle of resolution) VA was −0.08 (±0.06) at 94 cd/m, 0.05 (±0.07) at 3 cd/m, 0.16 (±0.06) at 0.75 cd/m, and 0.27 (±0.09) at 0.38 cd/m. Light level and accommodative error were significantly associated with VA, and light level explained 75% of the variance. The mean differences in VAs between two visits were not significantly different from zero (p > 0.05). The coefficients of repeatability for 94, 3, 0.75, and 0.38 cd/m were 0.08, 0.11, 0.14, and 0.14 logMAR, respectively. CONCLUSIONSLight level, among all other factors studied, contributes the most to the reduction in VA tested under mesopic conditions. Testing mesopic VA at 0.75 cd/m, or about 2.0 log units less than photopic testing, provides a significant and repeatable decrease in VA similar to standardized low-contrast VA testing, and therefore this level is recommended.